Practical PHP and MySQL web site databases - West, Adrian W.
Practical PHP and MySQL Website Databases is a project-oriented book that demystifies building interactive, database-driven websites. The focus is on getting you up and running as quickly as possible. In the first two chapters you will set up your development and testing environment, and then build your first PHP and MySQL database-driven website. You will then increase its sophistication, security, and functionality throughout the course of the book. The PHP required is taught in context within each project so you can quickly learn how PHP integrates with MySQL to create powerful database-driven websites